Slightly overcast. (Economist, 1996)
The prospect of Sun Microsystems taking over the troubled Apple Computer company appears to have faded, and some investors are looking more closely at Sun itself. Since the release of Java—its much-hyped computer language for the Internet—in 1995, the company has been doing well. Early in 1996, however, news leaked that three founding members of Sun's Java team were leaving the firm to set up their own company, writing Java software. In addition, there are concerns about how Sun will make money from Java's success: Sun gives away its user software, charging manufacturers only a small once-off fee and $2 for every machine they sell. Moreover, there are doubts about its traditional workstation business facing competition.